2007
DOI: 10.1182/blood-2006-10-049072
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of CXCL11 by CD13/aminopeptidase N impairs CXCR3 and CXCR7 binding and signaling and reduces lymphocyte and endothelial cell migration

Abstract: CXCR3 ligands were secreted by tissue fibroblasts and peripheral blood-derived mononuclear leukocytes in response to interferon-(IFN-) and Toll-like receptor (TLR) ligands. Subsequent purification and identification revealed the presence of truncated CXCL11 variants missing up to 6 amino acids. In combination with CD26/dipeptidyl peptidase IV, the metallo-protease aminopeptidase N (APN), identical to the myeloid cell marker CD13, rapidly processed CXCL11, but not CXCL8, to generate truncated CXCL11 forms. Trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
117
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 46 publications
4
117
0
Order By: Relevance
“…Identification of APN substrates implicated in tumor growth and metastasis is another required next step. A number of cytokines, growth factors, and extracellular matrix molecules implicated in angiogenesis have been reported as putative APN substrates (46)(47)(48)(49)(50)(51)(52)(53)(54)(55), and testing their possible roles in the models presented here will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of APN substrates implicated in tumor growth and metastasis is another required next step. A number of cytokines, growth factors, and extracellular matrix molecules implicated in angiogenesis have been reported as putative APN substrates (46)(47)(48)(49)(50)(51)(52)(53)(54)(55), and testing their possible roles in the models presented here will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The human COOH-terminal CXCL4/PF-4 peptide (CXCL4/PF-4 : NGRKICLDLQAPLYKKIIKKLLES) and CXCL4L1/PF-4var peptide (CXCL4L1/PF-4var : NGRKICLDLQALLYKKIIKEHLES) were prepared by solid-phase peptide synthesis using fluorenyl-methoxycarbonyl (Fmoc)-protected amino groups as previously described (22). Purification was done by reversed-phase high-performance liquid chromatography (RP-HPLC) using a Source 5RPC column (GE Healthcare).…”
Section: Peptide Synthesismentioning
confidence: 99%
“…Human synthetic CXCL11/I-TAC (22) and natural human CCL2/MCP-1, purified in our laboratory (23), were used as positive controls. Chemotaxis of activated T cells was done in HBSS supplemented with 0.1% (w/v) HSA at 2 × 10 6 cells/mL in the Boyden microchamber (Neuro Probe) with fibronectin-coated, polyvinylpyrrolidone-free polycarbonate membranes (5-μm pore size; Corning Separations Division) for 3 h at 37°C.…”
Section: In Vitro Chemotaxismentioning
confidence: 99%
“…Previous reports have shown that CXCL10 is cleaved at the carboxyl terminus by furin in the cellular context (45), and that CXCL9 and CXCL10 can be truncated at the carboxyl terminus by MMP-8 and MMP-9 (28), however, no functional changes were found for any of these cleavages. Like many chemokines, CXCL11 is cleaved at the amino terminus after proline 2 by dipeptidylpeptidase IV (46,47) and aminopeptidase N (14), resulting in loss of agonism, but the propensity of MMPs in processing this chemokine are unknown. Here, we have biochemically screened all CXCR3 ligands for MMP processing by evaluating CXCL9, CXCL10, and CXCL11 as leukocytic-MMP substrates and report that CXCL11 is processed by several MMPs resulting in altered receptor binding and glycosaminoglycan affinity.…”
mentioning
confidence: 99%
“…Cleavage of proteoglycan core protein also disrupts chemokine gradients formed by chemokine binding to the glycosaminoglycan side chains (13). A variety of proteases are thought to be involved in chemokine cleavage including CD13, also known as aminopeptidase N (14), CD26, also known as dipeptidylpeptidase IV (15,16), dipeptidylpeptidase-8 (16), neutrophil elastase (17), cathepsin G (18), cathepsins B and D (19), and the matrix metalloproteinases (MMPs) 2 (reviewed in Refs. 20 -22).…”
mentioning
confidence: 99%